Evaluation of the Boxing Sports Development Programme in South Barito Regency - Sinta Gistati; Cerika Rismayanthi (FKIP - Universitas Riau, 2026)
Boxing is a priority sport in South Barito Regency, yet the effectiveness of its athlete development programme needs systematic evaluation to ensure resources and implementation meet athletes’ needs. This study evaluated the programme using the CIPP model (context, input, process, product). A quantitative descriptive design involved 32 respondents (27 athletes, 3 administrators, 2 coaches). Data were obtained through questionnaires, interviews, and observations and analysed descriptively. Context results showed programme management and needs were rated good–very good (positive ratings: administrators 67%, coaches 50%, athletes 79%). Input results indicated resources and facilities were adequate, with administrators mostly rating good (67%), coaches rating very good (54%), and athletes rating good (79%). Process results suggested implementation was effective (administrators good 67%, coaches very good 50%, athletes good 67%). Product results reflected good training outcomes, supported by administrators (67%), coaches (very good 50%), and athletes (good 74%). Overall, the programme is effective, but improvements in facilities, funding continuity, and training-method innovation are needed to strengthen future athlete performance.